Influência da postura, do sexo e da idade sobre o padrão respiratório e movimento toracoabdominal em indivíduos saudáveis no repouso - Liliane Patricia de Souza Mendes (2015)
Background: Data from breathing pattern and thoracoabdominal motion provide important information of respiratory function, and thus, should be considered during physiotherapy assessment. Both depend of the compartmet compliance, and therefore are influenced by different factors, among which are the position, sex and age. Currently it is well known that different positions can influence the thoracoabdominal motion, however, there is a lack in literature regarding this influence on breathing pattern. Little is known about the effect of gender on the respiratory pattern and its influence on the kinematics of the chest wall remains controversial. Regarding influence of age, the literature suggests that it does not alter the breathing pattern and thoracoabdominal motion. Objective: To evaluate the effects of posture, sex and age on breathing pattern and thoracoabdominal motion during quiet breathing in healthy subjects. Method: 83 subjects of both genders, mean age of 42.72 ± 21.74 years old, body mass index of 24.56 ± 2.85 kg/m2 and with normal pulmonary function test were studied. Subjects were evaluated by optoelectronic plethysmography in three different positions: sitting, supine and supine with 45º of trunk inclination. To check the influence of the position and sex analysis of variance (ANOVA) with repeated measures mixed factorial was used, in a design of plots and subplots 3x2 (positions x sex, respectively). For age influence, we used the multiple linear regression model. A 5% significance level was adopted. The project was approved by the Research Ethics Committee of UFMG (ETIC 0194.0.203.000- 11). Results: The change from sitting to inclined and supine positions promoted a significant reduction of the chest wall volume (Vcw) and minute ventilation (MV) in both sexes, and this reduction was greater in males. The reduction of trunk inclination increased the percentage contribution of abdomen to tidal volume (Vab%), while the percentage contribution of RC to tidal volume (Vrcp%) increased significantly with the vertical trunk. Women had breathing pattern more thoracic compared to men. The variables chest wall end-expiratory volume (Veecw) and chest wall endinspiratory volume (Veicw) showed a significant reduction when changing from a sitting position to inclined position in both sexes and from sitting to supine, only in men. The variables respiratory frequency (f) and ratio of inspiratory time to total time of the respiratory cycle (Ti/Ttot) were not affected by changes in positions or gender. Between 21 and 85 years, it was observed that there is an average reduction of 0.20% and 0.08% in Vrcp% and in Vrca% associated with a mean increase of 0.29% in Vab% and 0.08% in Veecw and Veicw for each year increased in age. Conclusion: The results of this study suggest that posture, sex and age influence the breathing pattern and thoracoabdominal motion in healthy subjects at rest. The sitting position may benefit patients with reduced tidal volume for different reasons. Regarding the f, none of the positions provides changes in tachypnea. The degree of contribution from each compartment is dependent of posture and this may be beneficial to positional orientation of patients with a reduction in the expansion in any of those. The reduction of RC contribution to tidal volume with age, lead to the development of strategies to minimize the loss of volume on this compartment.